Vulvodynia, Genital Eczema and Lichen Sclerosus: What are the Successful Treatments from a Patient’s Perspective? - Berger VC; Fierz R; Kolm I; Leeners B; Betschart C (Dove Medical Press, 2024)
Vera Christina Berger,1,2 Ronja Fierz,2 Isabel Kolm,3 Brigitte Leeners,2,4 Cornelia Betschart1,2 1Department of Gynecology, University Hospital of Zurich, Zurich, Switzerland; 2Medical School, University of Zurich, Zurich, Switzerland; 3Department of Pathology, Lucerne Hospital, Lucerne, Switzerland; 4Department of Reproductive Endocrinology, University Hospital of Zurich, Zurich, SwitzerlandCorrespondence: Vera Christina Berger, Department of Gynecology, University Hospital of Zurich, Rämistrasse 100, Zurich, 8091, Switzerland, Tel +41432551111, Email vera.berger@usz.chBackground: Genital pain treatment regimens range from local or systemic pharmacological to non-pharmacological, manual and psychosexual therapies with poor to moderate evidence for their efficiency. The aim of this study was to evaluate the subjective therapeutic response (genital pain relief) of different treatment modalities for vulvodynia and the most prevalent other vulvar pathologies, chronic vulvar eczema and lichen sclerosus by means of a cross-sectional survey.Material and Methods: A questionnaire-based cohort study that included 128 vulvodynia, 116 eczema and 79 lichen sclerosus patients was used. All patients attended the vulvar clinic at the University Hospital of Zurich. The patients who had been treated were surveyed from January to October 2022, using a customized online questionnaire consisting of 37 questions on symptoms and treatment outcomes for guideline-recommended treatment modalities. The study was approved by the Cantonal Ethics Review Board of Zurich.Results: Altogether, 41 patients with vulvodynia, 37 with vulvar eczema and 23 with lichen sclerosus returned the questionnaire. The three groups were similar regarding pain characteristics and comorbidities. All three patient groups reported having benefited from non-pharmacological treatment (improvement rate vulvodynia 54%; eczema 51%; lichen sclerosus 58%), from topical (55%; 55%; 75%) and from locally invasive (46%; 66%; 50%) treatments. Overall, there was no significant difference in subjective treatment outcome between non-pharmacological, locally invasive, and topical treatments for vulvodynia, eczema, and lichen sclerosus. However, the use of oral medication was reported to be significantly less effective (p-value 0.050).Conclusion: In conclusion, we found that in the patients' perception, topical, invasive and non-pharmacological treatments, but not oral medications, are helpful for genital pain relief in women with vulvodynia, vulvar eczema, and lichen sclerosus. Therefore, we recommend an escalating therapy approach with first-line non-pharmacological treatments together with topical therapies.Keywords: genital pain, vestibulodynia, therapy, patient reported treatment outcome, survey